Producing non-dendritic A356 and A380 feedstocks: Evaluation of the effects of cooling slope casting parameters - Acar, Serhat; Guler, Kerem Altug (CARL HANSER VERLAG, 2020)
In this study, low superheat casting and cooling slope casting processes were carried out with A356 and A380 aluminum alloys in order to obtain feedstocks with near globular microstructures. Castings were conducted at 20 degrees C above of the liquidus temperature for both processes and molten alloys were cast through a copper cooling slope with two different lengths (350 mm and 650 mm) and two different tilt angles (30 degrees and 60 degrees). In order to evaluate the significance of boron nitride coating on cooling slope, castings in short slope were carried out under both coated and uncoated conditions. Microstructural examinations and hardness measurements were carried out. According to obtained results, cooling slope casting caused superior microstructural properties as compared to low superheat casting, especially for A356 alloy. 30 degrees tilt angle was found more efficient in order to obtain a more globular microstructure for A356, while, on the other hand, the tilt angle of 60 degrees was detected more favorable in that manner for A380. Obtained grain size measurements were slightly improved with the employment of short slope and coating was found beneficial especially for A356 alloy. The measured hardness values did not display any significant difference in the same alloy type except in the low superheat cast. A356 specimen, which was obtained with coarser microstructure.
Keywords: Cooling slope (CS) casting; low superheat casting (LSC); non-dendritic feedstock; aluminum alloy; Materials Science